2015
DOI: 10.1039/c4cp04849k
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable improvement in microwave absorption by cloaking a micro-scaled tetrapod hollow with helical carbon nanofibers

Abstract: Helical nanofibers are prepared through in situ growth on the surface of a tetrapod-shaped ZnO whisker (T-ZnO), by employing a precursor decomposition method then adding substrate. After heat treatment at 900 1C under argon, this new composite material, named helical nanofiber-T-ZnO, undergoes a significant change in morphology and structure. The T-ZnO transforms from a solid tetrapod ZnO to a micro-scaled tetrapod hollow carbon film by reduction of the organic fiber at 900 1C. Besides, helical carbon nanofibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 41 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…So, it has been found that microwave absorbing materials have important role in EM interference shields and radar absorbers. Polymers [1,2], carbon materials [3,4], ferrites [5,6], nonferrite ceramics [7,8], magnetic metals [9,10] and hybrid materials [11,12] have been investigated for their microwave absorbing properties. Different morphologies, complex hierarchical and heterostructured nanoparticles are also considered for their enhanced EM properties.…”
Section: Introductionmentioning
confidence: 99%
“…So, it has been found that microwave absorbing materials have important role in EM interference shields and radar absorbers. Polymers [1,2], carbon materials [3,4], ferrites [5,6], nonferrite ceramics [7,8], magnetic metals [9,10] and hybrid materials [11,12] have been investigated for their microwave absorbing properties. Different morphologies, complex hierarchical and heterostructured nanoparticles are also considered for their enhanced EM properties.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36] ZnO material has got wider applicability as a dielectric absorbent because of its light weight, semiconducting and piezoelectric features [37][38][39] as well as surface electric polarization effect 25 which is beneficial for microwave absorption. Earlier investigations on the microwave absorption properties of tetrapod-shaped ZnO based absorbers by Jian et al 48 and Zhang et al 49 showed a remarkable improvement in the EM wave loss characteristics, which indeed demonstrate their huge potential for utilizations in this field. [46][47] These unique features of ZnO tetrapods motivated us to use them as microwave absorbing materials as they have been rarely used in this respect, in fact from literature search reveals only very few studies.…”
Section: Introductionmentioning
confidence: 90%
“…1 Hence, it is of great importance to shield and absorb both the incoming and outgoing EM wave radiation around us. As a result, several kinds of materials have already been found to possess the EM wave absorption properties, for instance, magnetic particles (Fe 3 10 nanoparticles (Ag, Ni, Fe, Co, ZnO, CeO 2 ), [11][12][13][14] conductive polymers (PANI, PPy), [15][16][17] carbon materials (CNTs, graphene, graphite, carbon black, amorphous carbon, carbon fiber), 1,12,[18][19][20][21][22][23] metallic perovskite lanthanum nickel oxide, 24 and magnetic-dielectric hybrids. 2 Therefore, for the big demand in civil and military fields, EM wave absorption and shielding materials have already attracted a great deal of attention from all over the world and have already been widely investigated in both academic and industrial labs.…”
Section: Introductionmentioning
confidence: 99%